IDENTIFICATION OF SIDE CATCHING FISH (BYCATCH) GOMBANG FISHING GEAR IN MESKOM VILLAGE BENGKALIS DISTRICT RIAU PROVINCE - Sulaiman, Ahmad; Yani, Alit Hindri; Bustari, Bustari (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2020)
ABSTRACTÂ This research was conducted in October-November 2018 in Meskom village, Bengkalis District, Bengkalis Regency, Riau Province. The purpose of this research is to become a database for the types of fish caught bycatch (bycatch) fishing wagons that are operated in Meskom Village, Bengkalis District, Bengkalis Regency, Riau Province. The method used in study is a direct survey method by observing in the field by looking at fishing activities using a good fishing gear. Data collection is done by going directly to the field by carrying out arrests and interviews with good fisherman. Catches numbering 22 spesies consisting of various types of shrimp and fish. The total number of catches was 364,4 (kg) or as many as 328715 heads.Â Keywords :Gombang, Identification, Bycatch, Meskom Village